UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH TAX MINIMIZATION, DEBT COVENANT, KUALITAS AUDIT, EXCHANGE RATE TERHADAP TRANSFER PRICING - Sonya Enda Natasha S. Pandia; Robinhot Gultom (Universitas Methodist Indonesia, 2022)
This research aims to determine and analyze the influence of Tax Minimization, Debt Covenant, Audit Quality, dan Exchange Rate in Transfer Pricing. The populations in this research were 202 companies. The sampling method in this research was purposive sampling and obtained 51 sample companies. The data testing method used is multiple linear regression analysis with residual test testing.The result of analysis shows that simultaneously Tax Minimization, Debt Covenant, Audit Quality, dan Exchange Rate have a not significant effect on Transfer Pricing. Partially, Tax Minimization, Debt Covenant, Audit Quality, dan Exchange Rate have a not significant on Debt Policy. Firm Size is not a moderating variable because it is unable to strengthen or weaken the relationship between Tax Minimization, Debt Covenant, Audit Quality, dan Exchange Rate against Transfer Pricing.